Domestic Violence: Public Policy Concern and Measuring Challenge - Ilie, Simona (Calitatea Vieții, 2022)
As a complex, often recurring phenomenon that risks to remain undeclared, domestic violence is a problem that has been recently approached on its own terms by the Romanian public policy. There are currently several series of statistical data provided by the institutions that are entrusted with fighting domestic violence. The combined analysis of these data creates a puzzling image about the phenomenon. This study includes a diagnosis of the phenomenon over the past years and explores the relationship between public policy and the dynamic of the phenomenon in periods of building up the integrated monitoring system. In apparent contradiction with the qualitative perception of the COVID-19 pandemic as favoring factor, the study identifies the differentiated impact of the pandemic on domestic violence over the period 2020−2021.